Highways to Success or Byways to Waste : Estimating the Economic Benefits of Roads in Africa - Ali, Rubaba; Barra, A. Federico; Berg, Claudia; Damania, Richard; Nash, John; Russ, Jason (Washington, DC: World Bank; and Agence Française de Développement, 2015)
Roads are the arteries through which the world’s economies pulse. Roads connect sellers to markets, workers to jobs, students to education, and the sick to hospitals. Yet in much of the developing world—and particularly in Africa—adequate roads are lacking. Accordingly, investment in transportation remains a key strategy for development agencies. Roughly $6.8 billion per year is spent in Sub-Saharan Africa on paving roads, and the World Bank invests more on roads than on education, health, and social services combined.